Bullet hole constellations: Berlin's Neues Museum, a case study in cultural memory - Dolgoy, RC (2014)
This dissertation explores a shift in cultural memory theory and praxis that loosely coincides with the turn of the century. With Berlin as its focus, I trace this shift through three of its museum institutions (the Jewish Museum, the Masterplan Museumsinsel, and the Neues Museum). I specifically look at three aspects: their museum practices (how history is expressed), the main narratives embodied in their spaces (what history is being expressed), and the critical contexts in which they are embedded (what do these practices and narratives mean in the wider cultural context). Throughout, I develop the idea of a cultural memory that emphasizes how we use the past, or what we do with our cultural inheritance. This runs counter to the cultural memory that sees remembering as a categorical imperative ('never forget' or 'lest we forget'), a memory that is clearly embodied in Libeskind's Jewish Museum and is typified in critical work that either prioritizes trauma (Caruth, LaCapra) or stresses cultivating specific empathetic responses (Landsberg's 'prosthetic memory,' Hirsch's 'postmemory'). My cultural memory hypothesis fits within the general German field of Cultural Memory Studies, as typified in the work of Jan and Aleida Assmann. The outcome of thinking about memory as use, appropriation, and transformation of cultural inheritance is the characterization of the past as an analytical tool. This notion sits well amidst current work by Dekel and Arnold-de Simine who read museum/memorial spaces as facilitators of civic engagement. This new cultural memory can be found embodied in the architectural and curatorial framing of the Neues Museum, in its phenomenological approach to history, its narrative of fragmentary wholeness, as well as in its placing of the twentieth century in long narratives of historical continuity. These characteristics allow me to read the Neues Museum as an example of contemporary thinking about modernism, and thus as part of a discourse that looks to restore and transform crucial mythological tendencies.